2002
DOI: 10.1254/jjp.90.328
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Suppression of Th2 Differentiation in the Anti-allergic Effect of Sho-seiryu-to in Mice

Abstract: The clinical effectiveness of the Kampo medicine Sho-seiryu-to (SST) has recently been demonstrated in a double-blind randomized study of allergic asthma and rhinitis. We investigated the effect of SST on a type 1 allergic model in mice. Ovalbumin (OVA)-induced sneezing and the total and OVA-specific IgE levels were significantly suppressed with SST at 1.0 g/kg, but that of OVA-specific IgG(2a) was not. In the splenocytes isolated from SST-administered mice, OVA-induced interleukin (IL)-4 production decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 13 publications
2
28
1
Order By: Relevance
“…With sho-seiryu-to, CD86 major histocompatability complex II cells and CD28CD4 T cells were selectively suppressed, shifting the Th1/Th2 ratio toward a Th1 response and resulting in decreased IL-4 and allergen-specifi c IgE production with no effect on interferon-γ. This was consistent with the improvement in allergen-specifi c sneezing in mice [24].…”
Section: Kampo Medicine (Japanese)supporting
confidence: 86%
“…With sho-seiryu-to, CD86 major histocompatability complex II cells and CD28CD4 T cells were selectively suppressed, shifting the Th1/Th2 ratio toward a Th1 response and resulting in decreased IL-4 and allergen-specifi c IgE production with no effect on interferon-γ. This was consistent with the improvement in allergen-specifi c sneezing in mice [24].…”
Section: Kampo Medicine (Japanese)supporting
confidence: 86%
“…This result suggests that SST shows antiallergic effects on immune systems in bronchoalveolar (BA) cavities but not on systemic immune responses. Recently, Ikeda et al [18] reported that OVA-specific IgE level in the serum and production of IL-4 in the splenocytes was suppressed by a pharmaceutical preparation of Sho- Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
“…From a scientific point ofview, anti-inflammatory effects of SST have been shown in humans assessed in a double-blind randomized study on patients with allergies such as bronchial asthma and allergic rhinitis (7). Furthermore, there are several in vivo reports concerning SST immunomoduratory action on allergic pathology, such as suppression of Th2 differentiation at the level ofsynapse between antigenpresenting cells and CD4+ T cells (7), inhibition of histamine signaling targeting its receptor expression and synthesizing enzyme (8), and augmentation of NGF induction accompanied by allergic pathology.…”
Section: Discussionmentioning
confidence: 99%